2018
DOI: 10.1039/c7nr07819f
|View full text |Cite
|
Sign up to set email alerts
|

Stable nanoconjugates of transferrin with alloyed quaternary nanocrystals Ag–In–Zn–S as a biological entity for tumor recognition

Abstract: One way to limit the negative effects of anti-tumor drugs on healthy cells is targeted therapy employing functionalized drug carriers. Here we present a biocompatible and stable nanoconjugate of transferrin anchored to Ag-In-Zn-S quantum dots modified with 11-mercaptoundecanoic acid (Tf-QD) as a drug carrier versus typical anticancer drug, doxorubicin. Detailed investigations of Tf-QD nanoconjugates without and with doxorubicin by fluorescence studies and cytotoxic measurements showed that the biological activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…This type of research is highly desirable in the case of quaternary Ag–In–Zn–S nanocrystals, especially, because by changing their composition it is possible to tune their efficient luminescence over the whole visible spectral range. This strongly facilitates their application in electronics and biomedical sciences. The analysis of ligand exchange-induced photoluminescence changes is especially important in this respect. In the case of binary CdSe nanocrystals the luminescence is governed by the classical radiative recombination mechanism 1S­(e) → 1S­(h).…”
Section: Introductionmentioning
confidence: 99%
“…This type of research is highly desirable in the case of quaternary Ag–In–Zn–S nanocrystals, especially, because by changing their composition it is possible to tune their efficient luminescence over the whole visible spectral range. This strongly facilitates their application in electronics and biomedical sciences. The analysis of ligand exchange-induced photoluminescence changes is especially important in this respect. In the case of binary CdSe nanocrystals the luminescence is governed by the classical radiative recombination mechanism 1S­(e) → 1S­(h).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorometric measurements were performed using Scinco-FS2 spectrofluorometer (Scinco, Seoul, South Korea) with low volume (200 µL) optical cuvette (Product no. 16.100 F/Q/10 from Starna Scientific, Co, Ilford, UK) compatible in terms of size and aperture position with the apparatus.…”
Section: Applied Characterization Methodsmentioning
confidence: 99%
“…QDs are spherical semiconductor NPs with versatile surface chemistry, which can be modulated. They have high potential in various biological applications, including bioimaging and drug delivery systems [15,16]. Furthermore, QDs have many superiorities compared to other drug carriers, such as larger specific surface area, smaller size, and stronger adsorption capacity [17].…”
Section: Introductionmentioning
confidence: 99%
“…showed that Ag–In–Zn–S QDs nanocrystals which were decorated with L−cysteine, 11−mercaptoundecanoic acid (MUA), and lipoic acid modified with folic acid (FA) can be employed as a good approach for engaging doxorubicin (DOX) to FRs in A549. The QD–MUA–FA–DOX complex had a great genotoxicity and cytotoxicity, and also inhibited the migration of A549 significantly ( 22 ).…”
Section: Bioapplications Of Qds In Lungmentioning
confidence: 99%